2014
DOI: 10.1007/s11096-014-9919-8
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perceptions and attitudes toward clinical pharmacy services in urban general hospitals in China

Abstract: From the perspective of improving physicians' overall attitudes, the prioritization strategy of developing CPSs in China should focus on the role of clinical pharmacists within the decision support system for medication management, thus encouraging clinical pharmacists to interact more frequently with physicians at the ward level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 14 publications
5
33
1
Order By: Relevance
“…The level of agreement in general appeared to be a function of the professionals’ year of experience, which is in line with a report that came out from West Virginia [ 8 ]. The present study also revealed that majority of the respondents had a positive attitude towards the changing role of pharmacists in their health care setting, which is concordant with a report from China [ 10 ], but discordant with that of Palestine [ 17 ]. According to the latter report, physicians in Palestine were more likely to accept traditional pharmacy services than newer clinical services.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The level of agreement in general appeared to be a function of the professionals’ year of experience, which is in line with a report that came out from West Virginia [ 8 ]. The present study also revealed that majority of the respondents had a positive attitude towards the changing role of pharmacists in their health care setting, which is concordant with a report from China [ 10 ], but discordant with that of Palestine [ 17 ]. According to the latter report, physicians in Palestine were more likely to accept traditional pharmacy services than newer clinical services.…”
Section: Discussionsupporting
confidence: 88%
“…There is a body of evidence in the literature showing that physicians are receptive to several clinical services provided by pharmacists and had a positive overall attitudes if these services were provided in the form of consultations or in a supportive manner [ 8 10 ]. However, other studies reported the existence of physicians’ resistance to the role of clinical pharmacists, which might have been attributed to lack of physicians’ exposure to pharmacist participation in clinical activities [ 11 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We incorporated minor modifications (with the permission of the authors). [10][11][12][13][14][15][16] Based on the literature of similar studies with the same research questions in the Gulf region and worldwide, the questionnaire was created in four domains in addition to participant's demographics:…”
Section: Survey Instrument Development and Implementationmentioning
confidence: 99%
“…Reports of pharmacy students' and physicians' attitudes toward clinical pharmacy and interprofessional collaboration have been documented in various countries, but these concepts have yet to be explored in South Africa . In Qatar, pharmacy students reported having an overall positive attitude toward pharmaceutical care but also felt that providing pharmaceutical care takes too much time and effort .…”
Section: Introductionmentioning
confidence: 99%